Endogenous allocation of the exit option between workers and shareholders - Michele Moretto; Gianpaolo Rossini (Fondazione Eni Enrico Mattei (FEEM), 1997)
We deal with efficient allocation of the shut-down decision of a firm in which there is profit sharing. The paper can be considered as a complement to the literature on the endogenous ownership structure of the firm. We examine a variety of cases according to both different schemes of layoff compensation and various degrees of specificity of human and physical capital. It appears that there are circumstances in which granting workers the decision to close can maximise the total payoff accruing to both contenders, with respect to the usual practice of shareholders decision making. Traditional conduct reveals an inefficiency that may add to the well known principal-agent concern. Leaving the decision to close to shareholders gives rise to a dead-weight loss, since a failure arises in the internal market for highly specific factors. Loss of control over the decision to exit is costly for shareholders. Proper compensation schemes can be devised for efficient transfer and/or sharing of the closing decision.
Keywords: L20; D92; 330; Liquidation; Eigentümerstruktur; Mitarbeiterkapitalbeteiligung; Gewinn; Allokationseffizienz; Theorie